Analisis Perencanaan Produksi Agregat pada CV. Pelangi Rex’s di Denpasar - Pramodya Utami, Anak Agung Istri Riska; Mandala, Kastawan (Universitas Batanghari Jambi, 2024)
The production function in every company has a very important role in developing a business, especially in the industrial sector. This study aims to determine the aggregate production planning strategy that has the lowest cost at CV. Rainbow Rex's. This type of research uses a quantitative descriptive approach. Data collection methods used are interviews and observation. Data analysis techniques are performed by forecasting demand using the Moving Average and Exponential Smoothing Methods, and the aggregate planning methods used are the Chase Strategy, Level Strategy, and Mixed Strategy. Based on the research results, the selected forecasting calculation for Croissant products is the Moving Average and Fresh Bread products in the selected forecasting calculation, namely the Exponential Smoothing method. The aggregate production planning strategy that has the lowest total cost for Croissants and Fresh Bread is the Chase Strategy. The implication of this research is to add references for academics who conduct research on aggregate production planning and can be used as material for company considerations in carrying out production planning.